2000
DOI: 10.1006/dbio.2000.9741
|View full text |Cite
|
Sign up to set email alerts
|

Gpbox (Psx2), a Homeobox Gene Preferentially Expressed in Female Germ Cells at the Onset of Sexual Dimorphism in Mice

Abstract: XX gonads differentiate into ovaries, a morphologic event evident by embryonic day 13.5 (E13.5) in mice. To identify early markers of oogenesis, sex-specific urogenital ridge cDNA libraries were constructed from E12-13 embryos. After mass excision and isolation of plasmid DNA, approximately 4800 expressed sequence tags were determined and compared to existing databases. Few cDNAs were specifically expressed in the urogenital ridge, but one, designated GPBOX, encodes a 227-amino-acid homeobox protein that is fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 59 publications
1
54
0
Order By: Relevance
“…Genomic sequence data base searches with Ehox cDNA sequences has revealed a number of regions that are identical to sequences from the murine X chromosome, confirming this as the chromosomal location of Ehox. This is in keeping with the presence of other paired-like genes on this chromosome in the mouse (27).…”
Section: A Clone From An Es Cell Subtracted Library Encodes a Fragmensupporting
confidence: 84%
“…Genomic sequence data base searches with Ehox cDNA sequences has revealed a number of regions that are identical to sequences from the murine X chromosome, confirming this as the chromosomal location of Ehox. This is in keeping with the presence of other paired-like genes on this chromosome in the mouse (27).…”
Section: A Clone From An Es Cell Subtracted Library Encodes a Fragmensupporting
confidence: 84%
“…By contrast, Rhox9-null mice were not found to have any observable defects (Takasaki et al 2001). One explanation is that the functions of Rhox9 are compensated for by Rhox6, as these two genes are highly similar in sequence and expression pattern (Chun et al 1999, Takasaki et al 2000. But if Rhox6 does compensate for Rhox9, it does so without being upregulated, as Rhox6 mRNA is not increased in level in trophoblast cells, the testis, or ovary of Rhox9-null mice (Takasaki et al 2001).…”
Section: Expression and Functional Role Of Rhox Cluster Genesmentioning
confidence: 99%
“…The expression of Rhox genes in ES cells was determined by northern blot analysis (Sasaki et al 1991, Fan et al 1999, qPCR analysis (Jackson et al 2002, Fouse et al 2008, and semi-quantitative PCR analysis (Oda et al 2006). The expression of Rhox genes in the early embryo (blastocyst to E8.5) was determined by semiquantitative PCR analysis (Takasaki et al 2000, Jackson et al 2002, Chazaud et al 2006; while Rhox6 and Rhox9 cannot be detected in normal mouse embryos, they can be detected in Dnmt-mutant embryos deficient in DNA methylation by RT-PCR (33 cycles; Oda et al 2006). The expression of Rhox genes in fetal gonads was determined by qPCR and in situ hybridization analyses (Daggag et al 2008); these analyses demonstrated that all Rhox genes are predominantly expressed in primordial germ cells (PGCs), except for Rhox8, which was exclusively expressed in gonadal somatic cells (s).…”
Section: In Vivo Rhox5 Functionsmentioning
confidence: 99%
See 2 more Smart Citations